Serafim da Silva Neto: entre a constituição e a circulação do conhecimento linguístico - Schneiders, Caroline Mallmann (2014)
In this dissertation, we analyze how the memory domain of Linguistics is resumed and articulated in the discursive constitution, emphasizing the echoes and the signification soundings of the already said registered in the line of discourse. We aim to understand the way how the discursive process is historically determined, besides the way how certain notions of Linguistics, present in the Cours de linguistique générale, are repeated and/or modified as they are resumed in another sociohistorical and ideological conjuncture. From this, we aim the crossing of linguistic knowledge which belong to other conjunctures and return chaining in the discursive formulation as an effect of interdiscourse on itself, that is, by the functioning of the transverse-discourse. For this, we delimitated as temporal snip, the fifties, from XX century, once it was a fruitful moment in studies related to the Portuguese language and in linguistic researches which begin in the academic environment and we mobilized as file search some works by Serafim da Silva Neto: Introdução ao Estudo da Língua Portuguêsa no Brasil (1950); Manual de Filologia Portuguêsa (1952); Introdução ao Estudo da Filologia Portuguêsa (1956); História do Latim Vulgar (1957); Língua, Cultura e Civilização (1960). The corpus of analysis is composed by discursive passages from these works, whose choice criterion was the reference to two essential Saussure s dichotomies: language vs. speech and synchrony vs. diachronic. The mobilized analytical procedure is constituted by the moving among quote, the discursive paraphrase and the transverse-discourse. We begin from Course s quote which allows us to analyze the discursive paraphrase s functioning, that, on the other hand, enables the effect instauration of the transversediscourse in the discursive constitution, since, through the discursive paraphrase; we demonstrate the crossing and the articulation of other knowledge in the discourse horizontality by the repetition/reformulation and/or the signification soundings. This proposed analytical motion gives the basis to our thesis, giving light to the functioning of the transverse-discourse, which concern us, in a particular way, by allowing the reflection about the historical and sense filiations inscribed in the production of linguistic knowledge that we analyzed. Our research is affiliated to the History of Linguistic Ideas linked to the theoretical and methodological apparatus of Discourse Analysis of Pecheuxtian orientation, as both are being carried out in Brazil, in the last times.